PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PADA KARYAWAN TETAP PERUMDA AIR MINUM TIRTA BALURAN KABUPATEN SITUBONDO DENGAN ETOS KERJA SEBAGAI VARIABEL MODERATING - Husain, Putri Nur Alika; Pramesthi, Riska Ayu; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2024)
Regional Public Company (Perumda) of Air Minum Tirta Baluran Situbondo Regency is a regional drinking water company committed to providing clean, healthy and affordable drinking water for the people of Situbondo Regency, East Java. This study aimed to analyze and test the effect of work discipline and work environment on performance in permanent employees of Regional Public Company (Perumda) of Air Minum Tirta Baluran Situbondo Regency with work ethic as a moderating variable. The population in this study were permanent employees of the Regional Public Company (Perumda) of Air Minum Tirta Baluran Situbondo Regency. Sampling technique using a saturated sampling technique. This study's data analysis and hypothesis testing used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application show that work discipline has a significant positive effect on performance, work environment has a considerable positive impact on performance, work ethic has a negative but insignificant effect on moderating the relationship between work discipline variables on performance, work ethic has a positive but insignificant effect on moderating the relationship between work environment variables on performance.